Strategi Efektif dengan Menggunakan Aplikasi Quiziz dalam Pembelajaran Maharah Kitabah - Hafidz Hilfan Din Akbar; Ahmad Mujahid Ghoffar; Aufan Niam; Laili Mas Ulliyah Hasan (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to examine the effectiveness of using the Quizizz application in teaching writing skills (maharah al-kitabah) to students at Madrasah Tsanawiyah. Writing is one of the essential Arabic language competencies that requires intensive practice and appropriate media approaches for optimal learning. In the digital era, the use of technology-based media such as Quizizz is considered effective in increasing students' motivation and engagement. This research adopts a descriptive qualitative approach using observation, interviews, and documentation techniques. The findings indicate that the use of Quizizz enhances students’ enthusiasm for learning, enriches the variety of exercises, and develops critical thinking in Arabic writing. Theoretically, these findings align with constructivist learning theory and previous studies that show interactive media can promote productive language skills. The implication of this study highlights the importance of integrating digital media into the Arabic language curriculum, particularly in developing writing proficiency. The appropriate strategy in using Quizizz also assists teachers in designing more enjoyable and effective learning experiences.